2022
DOI: 10.3390/molecules27103193
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease in Long-Term Type 2 Diabetes: Role of rs738409 PNPLA3 and rs499765 FGF21 Polymorphisms and Serum Biomarkers

Abstract: Fibroblast growth factor 21 (FGF21) signaling and genetic factors are involved in non-alcoholic fatty liver disease (NAFLD) pathogenesis. However, these factors have rarely been studied in type 2 diabetes mellitus (T2D) patients from admixed populations such as in those of Brazil. Therefore, we aimed to evaluate rs738409 patanin-like phospholipase domain-containing protein (PNPLA3) and rs499765 FGF21 polymorphisms in T2D, and their association with NAFLD, liver fibrosis, and serum biomarkers (FGF21 and cytoker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…On the other hand, a shorter (4-week) exercise training intervention did not reduce either ALT or CK-18 despite decreasing postprandial insulin [ 58 ]. Similarly, in a study involving diabetic type 2 patients, serum levels of both FGF-21 and CK-18 were not evidently associated with the presence of NAFLD or liver fibrosis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a shorter (4-week) exercise training intervention did not reduce either ALT or CK-18 despite decreasing postprandial insulin [ 58 ]. Similarly, in a study involving diabetic type 2 patients, serum levels of both FGF-21 and CK-18 were not evidently associated with the presence of NAFLD or liver fibrosis [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) in genes are potentially involved in oxidative stress, lipogenesis de novo, and IR have an important role in the development and progression of NAFLD (11,12) . Polymorphism in the Patatin-like phospholipase domain containing 3 (PNPLA3) gene has an important impact on the susceptibility of NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this buccal problem can be transmitted vertically from pregnant women to newborns by influencing the establishment of the buccal microbiome of newborns [ 4 ]. Mauy Frujuello Mana’s [ 5 ] has found that the prevalence of non-alcoholic fatty liver disease in type 2 diabetic patients was as high as 88.6%, of which more than 1/4 of patients had significant liver fibrosis. Hyperglycemia induces the accumulation of sorbitol, causing increased moisture in nerve cells, diffuse swelling of nerves, obscuration of the perineural structures of nerve fascicles, reduced elasticity, increased hardness, leading to a series of peripheral nerve diseases [ 6 ] .…”
Section: Introductionmentioning
confidence: 99%